The Evolution of English Medium Instruction Research in Higher Education: A Bibliometric Study - Akmaral Karabay; Naureen Durrani (MDPI AG, 2024)
The expansion of English medium instruction (EMI) in higher education has generated significant scholarly interest, resulting in an increasing body of research across different contexts. This bibliometric study examines 1522 publications in the Scopus database to explore the intellectual, conceptual, and social structure of the EMI literature in higher education. Findings revealed substantial growth in publications and citations between 1974 and 2024, showing a notable increase in productivity after 2018. Most cited authors focus on EMI within their affiliated country, but some affiliated with British universities have made global contributions. The field exhibits global coverage, albeit with strong dominance by China, Spain, the UK, Australia, and Hong Kong, as well as limited representation from African nations, barring South Africa. EMI networks are primarily driven by authors' current and past institutional affiliations as well as geographical proximity, with the UK, Spain, and China emerging as leaders in these networks. The most productive journals focus on multilingualism, bilingualism, language policy, teaching, and learning while also encompassing higher education and multidisciplinary areas. Key topics signal a shift towards translanguaging and classroom interaction. Under-researched areas include (post)colonialism and EMI implementation. These findings provide a comprehensive insight into the evolving landscape of EMI research and potential future directions.